Lattice Constant Effect on Diffracted Transmission of ITO Periodic Nanostructures and Improvement of the Light Extraction Efficiency of Light-Emitting Diodes - Zhanxu Chen; Runhong Ding; Feng Wu; Wei Wan (Micromachines, 2021)
We studied the effects of the lattice pitch of indium-doped tin oxide (ITO) periodic nanostructures on the diffracted transmission to improve the light extraction efficiency of light-emitting diodes (LEDs). Periodic hexagonal ITO nanopillars with lattice constants of 600, 800, 1050, 1200, and 1600 nm were fabricated on ITO electrodes. We found that the light extraction efficiency strongly depended on the lattice constant. The LEDs with a lattice constant of 800 nm ITO nanopillars showed an increase in light extraction of 83%. In addition, their electrical properties were not degraded compared to conventional LEDs. The dependence of the extraction efficiency on the lattice constant was also calculated using a 3D finite-difference time-domain (FDTD) method, and this dependence was in good agreement with the experimental measurements. The transmission of each diffraction order and with the total transmission of ITO nanopillars with different lattice constants were calculated using the FDTD method to investigate the enhancement effect.